Transition to Parenthood and Marital Satisfaction: A Meta-Analysis - Bogdan, Ionela; Turliuc, Maria Nicoleta; Candel, Octav Sorin (Frontiers in Psychology, 2022)
The transition to parenthood is a major life event characterized by profound changes for a considerable number of people. Previous meta-analyses summarized the results obtained by various researchers in the first year and, respectively, in the first two years postpartum, globally. The current study adds to the literature by testing the changes from 12 to 24 months, the cross-partner associations and the analysis of different moderators. The aims of this present meta-analysis are to investigate the decrease in marital satisfaction during the first and second year postpartum, to examine cross-partner associations of the decline in postpartum marital satisfaction, and to investigate the potential moderating variables of this decrease. 49 studies (97 samples of parents and 9 samples of non-parents) that fit our criteria are included in the meta-analysis. The data analysis was performed using meta-analytic techniques. Marital satisfaction has a medium decrease between pregnancy and 12 months postpartum, and a small decline between 12 and 24 months postpartum for both genders. In a similar period with first year postpartum, non-parents present a small decline in marital satisfaction. Moreover, the analysis of the dyadic studies data shows cross-partner associations, confirming that one partner's satisfaction has a steeper decline when the other partner's satisfaction presents a steep decrease. The decrease in marital satisfaction does not stop after the first postpartum year, and the coss-partners associations are present. Theoretical and therapeutic implications are also discussed.